KINERJA SISTEM INFORMASI AKUNTANSI DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA (STUDI PADA PERUSAHAAN RITEL WILAYAH TANGERANG, TANGERANG SELATAN, JAKARTA, DAN BOGOR) - Osesoga, Maria Stefani (Ultimaccounting Jurnal Ilmu Akuntansi, 2020)
The purpose of this research is to obtain empirical evidence about the influence of user participation, accounting information system's user training education program, top management support, system development formalization, and information technology sophistication towards the performance of accounting information system. The object in this research is retail company in the Tangerang, Tangerang Selatan, Jakarta, and Bogor which use accounting information system. Data used in this research was primary data from questionnaires. There were 153 respondents consists of employees at retail company that already use accounting information system. Data analysis techniques in this study using multiple linear regression. The results of this research are: (1) user participation had significant and positive affect toward the performance of accounting information system, (2) accounting information system's user training education program had no positive affect toward the performance of accounting information system, (3) top management support had significant and positive affect toward the performance of accounting information system, (4) system development formalization had no positive affect toward the performance of accounting information system, and (5) information technology sophistication had no positive affect toward the performance of accounting information system. Keywords: Accounting Information System's User Training Education Program, Information Technology Sophistication, System Development Formalization, Top Management Support, User Participation.